Accessory Lacrimal Duct Cyst - Valiyaveettil Babitha; Chellappan Prasannakumary; Kuzhippally Vallon Raju (Delhi Journal of Ophthalmology)
Accessory lacrimal duct cyst is a very rare disease, however it needs to be kept in the differential diagnosis of orbital mass lesions and lid swellings. This is especially important because lacrimal duct cyst has to be excised completely to prevent recurrence and malignant transformation.